How experiencing eudaimonic emotions through music shapes prosocial and altruistic behavior: introducing a Unified Model of Music-Listening-Induced Eudaimonia (UMMIE) - Tukachinsky Forster, Rebecca; Spitz, Daniel H.; Rabinowitch, Tal-Chen; Granot, Roni (Frontiers in Cognition, 2025)
This paper introduces the Unified Model of Music-Listening Induced Eudaimonia (UMMIE), which offers an integrated novel theoretical framework to explain how music listening promotes prosocial and altruistic outcomes. Drawing on communication and psychology research, UMMIE maintains that elicitation of eudaimonic emotions can be appraised inwards, towards oneself, and thus contribute to the individual's personal growth, wellbeing, and development, or outwards, by connecting to something bigger than oneself, to humanity in general, which could possibly then lead to enhanced prosocial and altruistic attitudes and behaviors. The model specifies musical, situational, and individual variables that serve as moderators and increase the likelihood of experiencing inwards or outwards effects of music listening. In this way, the current article organizes and synthesizes existing literature and offers a novel blueprint for future research.